Preliminary trials on Hyperspectral Imaging Implementation to Detect Mycotoxins in Dried Figs - Benalia, Souraya; Bernardi, Bruno; Cubero, Sergio; Leuzzi, Antonio; Larizza, Michele; Blasco, José (2017)
Very nutritional and healthy, dried figs constitute an appreciated food for local populations of the Mediterranean area. However, the incidence of mycotoxins in this product, mainly attributed to traditional and poor agricultural practices, has been widely demonstrated and may develop quickly if storage conditions are not suitable, exceeding maximum safety thresholds set by European Union regulations. Mycotoxin identification is currently achieved by means of destructive methods that need sample preparation, and moreover are expensive and time consuming. Early and reliable detection techniques are required to prevent high risks for humans. Hyperspectral imaging is currently used for quality evaluation and safety inspection of agricultural products and food. It has not been used for the detection of dried fig contamination but could be a promising tool to determine the best spectral bands that permit contaminated fruit to be identified and eliminated, especially when applied to postharvest automated processes. In this context, the present work deals with preliminary trials on the ability of hyperspectral imaging to identify contaminations with aflatoxins and ochratoxin A on dried fig of Cosenza (PDO, Protected Designation of Origin) fruit by analyzing UV-induced fluorescence. Artificially contaminated figs did not show any fluorescence while decayed figs emitted fluorescence between 450 nm and 490 nm. The obtained results highlighted important aspects to be considered in order to improve the applied methodology and carry out further researches on the present theme.